The Politics of Aesthetics: Ezra Pound’s Jefferson is Mussolini - Hélène Aji (Transatlantica)
Inscribed within the framework of Ezra Pound’s theory of the “luminous detail,” historical facts are placed under the sign of a highly idiosyncratic master narrative, which ties in with a politics of aethetics, after Jacques Rancière but also in keeping with Benjaminian evaluations of the political uses of aesthetics. Mainly focused on Jefferson and/or Mussolini and a comparative study of the American edition and its Italian translation Jefferson e Mussolini, this article considers the possibility of a Poundian perilous fascination for an aestheticized vision of politics, yoking together the conception of state and the construction of the poem, under similar demands of beauty and aesthetic elegance, at the expense of ethical imperatives.